Experimental investigation on the thermophysical properties of Paraffin wax/wheat husk composite for thermal energy storage - Yadav, Aman; Mahendran, S.; Pandey, A. K.; Sharma, Kamal; Tyagi, V. V. (Elsevier Ltd, 2024)
Organic phase change materials (PCM) exhibit poor volumetric latent heat storage capacity and have low thermal conductivity. Therefore, this study aims to develop a PCM composite with better thermal conductivity and latent heat by dispersing newly synthesized wheat husk microparticles in Paraffin wax (A-70) PCM via a two-step technique. As per the results, the developed composite materials latent heat and thermal conductivity were 217.1 J/g & 0.45 W/m K, which was 4.57 % and 66.66 % higher than base PCM, respectively. Moreover, after 500 thermal cycles, the newly synthesized composite was found to be thermally and chemically stable.